Reduction of Data Transmission Time Delay with Object Detection in Underwater Acoustic Sensor Network - Pragathi, M; Kumar, R (International Journal of Engineering and Technology, 2018)
Underwater acoustic sensor networks plays vital role in many applications such as monitoring underwater environment, location and object detection etc., In environment monitoring, the sensor nodes monitors the unwanted obstacles and transmits the information about the obstacles to Base Station(BS). The major problem is when sending data from two or more number of sensor nodes at same time the time delay in data transmission will be increased. In this project, to overcome the problem of end to end delay, mobile data collector is employed with waterproof ultrasonic sensor nodes in underwater acoustic Sensor network.Â Â